PENGARUH PENGGUNAAN CANVA TERHADAP BELAJAR MENULIS TEKS PROSEDUR - Wahyu Nugroho (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2023)
This study aims to identify the effect of Canva on learning to write student procedure texts at SMK Negeri 2 Trenggalek. This research design is in quantitative research and is conducted with quasi-experimental research. This research uses two types of variables. The first variable is Canva, which will affect the dependent variable. Which was goinh to get effect from dependent variable. The sample of this study is X grade students of SMK Negeri 2 Trenggalek. Researchers chose X RPL B as the control group and X AK B as the experimental group. Each class has thirty-six students, but the total number of students participating in this study is eighteen members in each class. The instruments used in this study were tests, there were pre tests and post tests. The researcher gave a pre test to both classes before conduchting the treatment. Then, the post test was given to both classes after the researcher applied the treatment in the experimental class. The test consists of questions that students must rewrite procedural text through Canva media. After the data is collected, the researcher will analyze the data using an independent sample T-Test. Before conducting an independent sample t-test, researchers must conduct a normality test: Based on the results of the data, the Sig. value in Saphiro-Wilk of experimental group 0.188 is greater than 0.05 and Sig. in Saphiro-Wilk of Control Group 0.036 is greater than 0.05. This means that the samples in this study are normally distributed. Based on the